2020
DOI: 10.20944/preprints202004.0322.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Supplements in the Treatment of Male Infertility: A Critical Review on Their Formulations and Use

Abstract: Background: Dietary supplements (DS) represent a possible approach to improve sperm parameters and male fertility. A wide range of DS containing different nutrients is now available. Although many authors demonstrated benefits from some nutrients in male infertility, their real effectiveness is still under debate. The aim of this study was to critically review the composition of DS using the Italian market as sample. Materials & Methods: Active ingredients and their minimal effective daily dose (mFED) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To date, many systematic reviews and meta-analyses revealed the impact of different interventions in male infertility (Kamischke and Nieschlag, 1999;Boivin, 2003;Lafuente et al, 2013;Giahi et al, 2016;Hosseini et al, 2019;Smits et al, 2019;Wang et al, 2019;Garolla et al, 2020). Though systematic reviews and pairwise meta-analysis are vital tools for decision makers for contriving guidelines and clinical protocols, they produce partial information, because amongst several accessible interventions merely few are examined in head-to-head comparisons (Greco et al, 2015;Tonin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many systematic reviews and meta-analyses revealed the impact of different interventions in male infertility (Kamischke and Nieschlag, 1999;Boivin, 2003;Lafuente et al, 2013;Giahi et al, 2016;Hosseini et al, 2019;Smits et al, 2019;Wang et al, 2019;Garolla et al, 2020). Though systematic reviews and pairwise meta-analysis are vital tools for decision makers for contriving guidelines and clinical protocols, they produce partial information, because amongst several accessible interventions merely few are examined in head-to-head comparisons (Greco et al, 2015;Tonin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%